Narrative policy framework analysis and stakeholder analysis on ownership policy in the banking sector for economic resilience - Swasana, Rizky Dea Alih; Munandar, Adis Imam; Subiyantoro, Heru (Journal of Economic Resilience and Sustainable Development, 2025)
Background: Foreign ownership policy in Indonesian Banking has been regulated by the Government through Law Number 10 of 1998 concerning Banking. Through this law, the opportunity for foreign investors to own banking shares or establish banks in Indonesia is increasingly open. The strong foreign ownership of a bank has the potential to hinder the supervision process of the bank concerned and the practice of good governance, as well as disrupt financial system stability as a whole and threaten the economic resilience of the Indonesian state. Methods: The researcher conducted an analysis by Narrative Policy Framework (NPF) analysis and stakeholder analysis on the Minutes of Meeting on the Process of Amending Law Number 7 of 1992 to Law Number 10 of 1998 concerning Banking. This research is descriptive analytical on data obtained from the results of observations, interviews, documentation, and analysis of research subjects. Findings: The results of the study indicate that the opening of opportunities for foreign ownership in changing laws is a short-term solution provided by the government. Risk analysis has shown that the scale of the risk level of foreign ownership policy up to 99 percent is at the level of medium and high risk. Stakeholder analysis shows that the Government and Parliament are parties that have a large interest and strength in foreign ownership policies in the Indonesian banking sector. Conclusion: The Government and Parliament need to review the banking laws that have been used for 21 years. The findings highlight the need for a more balanced and strategic approach to foreign ownership policies to safeguard Indonesia's financial system stability and economic resilience. Novelty/Originality of this Article: This study contributes to the limited literature on foreign ownership policies in Indonesian banking by employing the NPF to reveal the hidden narratives and political dynamics behind the legislative process.